Зміст покарань, пов'язаних із виправно-трудовим впливом - Березовська, Наталя Леонідівна; Березовская, Наталья Леонидовна; Berezovskaja, N. (My University, 2012)
The article is based on past and current legislation of Ukraine, the achievements of science criminal and criminal executive law has opinions about whether the content of sentences related to corrective labor infl uence the order of serving and execution of the sentence, socially useful labor, social and educational work, general and vocational education, public exposure.
Березовська Н. Л. Зміст покарань, пов'язаних із виправно-трудовим впливом /Н. Л. Березовська // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред..), Л. І. Кормич (заст. голов. ред..), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України ; НУ ОЮА. – Одеса : Фенікс, 2012. – Вип. 46. – С. 367-376.
Keywords: виправно-трудовий зміст покарань; покарання; кримінально-виконавче право України; исправительно-трудовое влияние наказаний; наказание; уголовно-исполнительное право Украины; Forced labor impact of penalties; punishment; criminally-executive law of Ukraine